Training in motivational interviewing improves cattle veterinarians' communication skills for herd health management. (17th April 2020) - Svensson, Catarina; Wickström, Hans; Emanuelson, Ulf; Bard, Alison M; Reyher, Kristen K; Forsberg, Lars
Abstract : Background: Communication skills to promote changes in management routines are especially important in veterinary herd health management (VHHM). Motivational interviewing (MI) is a communication methodology shown to be effective in stimulating client behaviour change. This study aimed to evaluate a 6‐month MI‐training programme for veterinarians. Methods: Thirty‐eight cattle veterinarians gathered in groups of four to eight at six workshops separated by 3–4 weeks, during which they read literature and practised their skills. MI skills were evaluated before and after training using audio recordings of role‐play conversations with professional actors. Recordings were coded using the MI Treatment Integrity Code (MITI) V.4.2.1. The effect of training was evaluated by 16 regression models. Participants filled in questionnaires about their experiences. Results: All participants improved their MI skills after training in at least one parameter and significant improvements were found in all but 3 of the 16 statistically evaluated MITI variables. The mean (25th–75th percentiles) ratings of the veterinarians' perceived relevance of MI skills in their work was 4.9 (4.0–6.0) and of their satisfaction with the programme was 5.1 (5.0–6.0) on a 6‐point Likert scale. Conclusions: Results show that MI training was perceived to be useful and relevant and successfully improved veterinarians' communication skills in VHHM.